Mathematical Modeling and Experimental Study on Thin Layer Drying of Strawberry - Akpinar, Ebru Kavak; Bicer, Yasar (Walter de Gruyter Gmbh, 2006)
This paper presents mathematical modeling and the thin layer convective drying of strawberry. The experiments are conducted at drying air temperatures of 60, 75 and 85 deg.C in drying air velocities of 0.5, 1 and 1.5 m/s in a convective cyclone type dryer. The data of sample mass, temperature and velocity of the drying air were recorded continuously during each test. The experimental drying curves show only a falling drying rate period. The main factor in controlling the drying rate was found to be the drying air temperature. Also, the experimental drying curves obtained were fitted to eleven mathematical models. The Modified Page (I) drying model was found to satisfactorily describe the drying curves of strawberry with a correlation coefficient (R) of 0.98042, chi-square (2) of 0.0035 and root mean square error (RMSE) of 0.0588. The constants and coefficients of this model could be explained by the effect of drying air temperature and velocity with a correlation coefficient (R) of 0.998. The effective diffusivity coefficient of moisture transfer varied from 4.528x10- 10 to 9.631x10- 10 m2/s over the temperature and velocity range in this study.
Keywords: mathematical modeling; thin layer drying; strawberry